The Effect Of Self-Actualization Needs And Workload On Employee Work Performance At The Bengkulu City Industry And Trade Office - Tamara Damayanti; Sri Ekowati (Penerbit Jurnal Indonesia, 2024)
The title of this study is the effect of self-actualization needs and workload on employee performance at the Bengkulu City Industry and Trade Office. This research is based on the importance of employee performance for public organizations. Employee work performance is influenced by several factors, including self-actualization needs and workload. This study aims to analyze the effect of self-actualization needs and workload on employee performance at the Department of Industry and Trade of Bengkulu City.This type of research is quantitative research with a descriptive approach. The population of this study were all employees of the Bengkulu City Industry and Trade Office. The number of research samples was 65 people. Data collection was done using a questionnaire. Data analysis techniques using multiple linear regression analysis techniques. The results of data analysis obtained multiple linear regression equations as follows: Y = 10.995 + 0.567 X1 - 0.406 X2. The results of the analysis show that the need for self-actualization has a positive and significant effect on employee performance (tcount = 7.757 and Sig. = 0.000) and workload has a positive and significant effect on employee performance (tcount = 5.582 and Sig. = 0.000). Simultaneously, self-actualization needs and workload have a significant effect on employee work performance (Fcount = 98.024 and Sig. = 0.000).It is recommended to the Bengkulu City Industry and Trade Office to be able to improve employee performance by increasing self-actualization needs and managing employee workload.